Efficacy of Rasaushadhis in Shalakya Tantra (AYUSHDHARA, 2023)
Shalakya tantra also called as Uttamanga as it deals with vital sense organs located above the Jatru (clavicle). In Ayurvedic system of medicine Rasa shastra is one of the branch deals with Rasa aushadis preparations which are very much useful and effective, various special processing techniques such as Sodhana, Marana etc have been done for removing the toxic effects and utilising them for therapeutic purpose. Some of the Kriyakalpa procedures which are prepared with Rasa aushadhi are like Anjana (Samudraphena varti, Sukhavathi varti), Bidalaka (Gairikadi bidalaka, Manashiladi bidalaka) etc and oral medication include Saptamruta lauha, Shirashoolavajra ras, Sutasekar ras, Laxmivilas ras, Kaphaketu ras etc are indicated. Rasa aushadis are gently absorbable and digestible thus provide quick action and potent response in various Urdhavajatrugata vikaras. Rasa Aushadis act as Rasayana therapy helps to attain longevity, immunity, sharpness of sense organs etc.